Tracing Ideas From Langley (1999): Exemplars, Adaptations, Considerations, and Overlooked. (April 2022) - Lerman, Michael P.; Mmbaga, Nick; Smith, Anne
Well-accepted methodological practices require thoughtful and appropriate use to avoid becoming mindlessly applied and distorted. We review how ideas from Langley's (1999) process data analysis article have been used in practice. By closely analyzing 176 empirical articles in management and organization journals from 1999 to 2019, we highlight how Langley's ideas have been applied in exemplary ways and adapted through bricolage (a central concept in qualitative methods). In many instances, we found that Langley's ideas have been given a cursory nod or have even been distorted (what we label as considerations ); thus, we recommend how to avoid replicating these applications. We discuss process data analysis tools from Langley's article that have been underused (labeled overlooked ) but that may be valuable in future process studies. Through our deep reading and review, we highlight how using Langley's ideas can enhance the transparency and trustworthiness of a qualitative process study and mitigate her ideas' movement toward a mindless template application.